An Update on Tunneled Pleural Catheters. Issue 4 (July 2015) - Marks, Michelle; Dotson, Travis; Bellinger, Christina
Abstract : Recurrent pleural effusions of both malignant and benign etiologies cause significant dyspnea and decreased quality of life for patients who are frequently near the end of life. Tunneled pleural catheters allow for outpatient management of these effusions. In this article, we review the current literature regarding the effectiveness and complications associated with tunneled pleural catheter use in benign and malignant conditions.